All Days 2011
DOI: 10.2118/150639-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design Approach and Early Field Performance for a Solvent-Assisted SAGD Pilot at Cold Lake, Canada

Abstract: ExxonMobil and its affiliate Imperial Oil Resources are currently operating a Solvent-Assisted Steam-Assisted Gravity Drainage (SA-SAGD) experimental pilot plant at Cold Lake, Canada. During pilot operation, up to 20 percent by volume of a light hydrocarbon solvent will be injected with dry steam in a dual horizontal well SAGD configuration. The pilot scope consists of two horizontal well pairs (four wells total), six observation wells, associated steam and solvent injection facilities, artificial lift, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The start-ups of the SAGD processes are the same for all of the cases. First, (1) the duration of the preheating process lasts 75 days under 250 • C. Second, the steam trap control is 10 • C. Third, the temperature of the steam is 250 • C and the steam quality is 0.9 [43][44][45][46][47][48]. The maximum production rate is 550 m 3 /day, which is the capacity of the production pump used in this field.…”
Section: Numerical Simulation Modelmentioning
confidence: 99%
“…The start-ups of the SAGD processes are the same for all of the cases. First, (1) the duration of the preheating process lasts 75 days under 250 • C. Second, the steam trap control is 10 • C. Third, the temperature of the steam is 250 • C and the steam quality is 0.9 [43][44][45][46][47][48]. The maximum production rate is 550 m 3 /day, which is the capacity of the production pump used in this field.…”
Section: Numerical Simulation Modelmentioning
confidence: 99%
“…Butane was employed as the solvent in the field for co-injection with steam. The project could be considered one of the world's largest application of enhanced thermal recovery methods and the results will provide considerable insight in technical and logistical challenges of Solvent-Assisted thermal methods (Boone et al, 2011;Dickson et al, 2011). It appears that the process was operated at pressure 2500-4000 Kpa with almost 15% by mass of Butane (McCormack, 2007).…”
Section: Field Testsmentioning
confidence: 99%
“…They concluded that low pressure multi-component ES-SAGD at the right concentration (mostly at low concentration) is fairly competitive with SAGD at a high pressure. Pathak et al (2010;2011) conducted a series of hot-solvent injection experiments. The energy requirements of SAGD experiments were reduced by 30-40% in all experiments.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinjection of steam and solvent could further widen the applicability of solvent to extra-heavy oil and bitumen reservoirs. A few pilot tests for the coinjection were reported in the literature (Gupta et al 2005;Gupta and Gittins 2006;Dickson et al 2011).…”
Section: Introductionmentioning
confidence: 99%